Deep-Saddle-Shaped Nanographene Induced by Four Heptagons: Efficient Synthesis and Properties - Borrisov, Boris; Beneventi, Giovanni Mariano; Fu, Yubin; Qiu, Zhen Lin; Komber, Hartmut; Deng, Qing Song; Greißel, Phillip; Cadranel, Alejandro; Guldi, Dirk Michael; Ma, Ji; Feng, Xinliang (Journal of the American Chemical Society, 2024)
The construction of multiple heptagonal rings in nanographene is the key step for obtaining exotic carbon nanostructures with a negative curvature and intriguing properties. Herein, a novel saddle-shaped nanographene (1) with four embedded heptagons is synthesized via a highly efficient one-shot Scholl reaction from a predesigned oligophenylene precursor. Notably, a quadruple [6]helicene intermediate was also obtained and isolated by controlling the Scholl reaction conditions. Interestingly, the single crystal structures of 1 display a saddle geometry induced by the four embedded heptagons, resulting in a deep curvature with a width of 16.5 Å and a depth of 8.0 Å. Theoretical calculations at the molecular level suggest a weak antiaromatic character of the heptagons in 1. Remarkably, compound 1 exhibits dual fluorescence from S1 and S2. The deep-saddle-shaped geometry in 1 defines host-guest interactions with fullerenes, which were explored in titration experiments and by theoretical methods. The resulting 1@C60 are stable and are subject to an electron transfer from photoexcited 1 to C60. Our current study underscores the influence of heptagon rings on the photophysical, self-assembly, and electron-donating properties of NGs.
CRIS-Team Scopus Importer:2024-10-18

Graphene Oxide-BODIPY Conjugates as Highly Fluorescent Materials - Reina, Giacomo; Beneventi, Giovanni Mariano; Kaur, Ramandeep; Biagiotti, Giacomo; Cadranel, Alejandro; Ménard-Moyon, Cécilia; Nishina, Yuta; Richichi, Barbara; Guldi, Dirk Michael; Bianco, Alberto (Chemistry - A European Journal, 2023)
Covalent functionalization of graphene oxide (GO) with boron dipyrromethenes (BODIPYs) was achieved through a facile synthesis, affording two different GO-BODIPY conjugates where the main difference lies in the nature of the spacer and the type of bonds between the two components. The use of a long but flexible spacer afforded strong electronic GO-BODIPY interactions in the ground state. This drastically altered the light absorption of the BODIPY structure and impeded its selective excitation. In contrast, the utilisation of a short, but rigid spacer based on boronic esters resulted in a perpendicular geometry of the phenyl boronic acid BODIPY (PBA-BODIPY) with respect to the GO plane, which enables only minor electronic GO-BODIPY interactions in the ground state. In this case, selective excitation of PBA-BODIPY was easily achieved, allowing to investigate the excited state interactions. A quantitative ultrafast energy transfer from PBA-BODIPY to GO was observed. Furthermore, due to the reversible dynamic nature of the covalent GO-PBA-BODIPY linkage, some PBA-BODIPY is free in solution and, hence, not quenched from GO. This resulted in a weak, but detectable fluorescence from the PBA-BODIPY that will allow to exploit GO-PBA-BODIPY for slow release and imaging purposes.
CRIS-Team Scopus Importer:2023-05-19
Keywords: carbon nanomaterials; chemical functionalization; imaging; photoluminescent properties; transient absorption spectroscopy

Intramolecular Singlet Fission in Individual Graphene Nanoribbons─Competition with a Charge Transfer - Greißel, Phillip; Beneventi, Giovanni Mariano; Weiß, René; Wollny, Anna-Sophie; Dubey, Rajeev K.; Melle-Franco, Manuel; Clark, Timothy; Mateo-Alonso, Aurelio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Graphene nanoribbons (NRs) constitute a versatile platform for developing novel materials, where their structure governs their optical, electronic, and magnetic properties while also shaping their excited-state dynamics. Here, we investigate a set of three twisted N-doped molecular NRs of increasing length, obtained by linearly fusing perylene diimide to pyrene and pyrazino- or thiadiazolo-quinoxaline residues. By employing various temperature-dependent time-resolved spectroscopy techniques, we reveal how the flexible twisted NR geometry promotes the formation of a mixed electronic state with varying contributions from locally excited and charge-transfer (CT) states. The fate of this mixed state is highly sensitive to the molecular geometry, length, and solvent polarity. For the shortest NR, intersystem crossing dominates the deactivation pathway, efficiently generating triplets in low-polarity solvents. In contrast, for the extended NRs, intramolecular singlet fission (SF) takes place within a single nanoribbon. This is enabled by enhanced superexchange coupling due to a pronounced push-pull nature and the existence of multiple localized π-electron states caused by heteroatom doping, thereby circumventing the need for dimeric interactions typically associated with conventional SF systems. In higher-polarity environments, evidence of a (diabatic) CT state emerges. These findings underscore the intricate relationship between geometry, energy levels, and excited-state dynamics in twisted N-doped NRs.
CRIS-Team Scopus Importer:2025-04-01

Laterally π-Extensed Nitrogen-Doped Molecular Nanographenes – From Anti-Kasha Emission to Ping-Pong Energy Transfer Events - Beneventi, Giovanni Mariano; Schöll, Kilian; Platzer, Benedikt; Krug, Marcel; Mai, Lukas; Negri, Fabrizia; Cadranel, Alejandro; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2024)
Nanographenes, which feature at least one dimension smaller than 100 nm, are drawing interdisciplinary attention. Understanding the interplay between structure and properties is, however, still in its infancy. Molecular nanographenes are much better suited to fill this knowledge gap than graphene quantum dots or nanoribbons. Their bottom-up synthesis allows atomic precision and, thereby, assists in handling structure and connecting it with properties. Herein, the effects of nitrogen-doping and lateral π-extension in molecular nanographenes and in their coordination complexes with ruthenium porphyrins are investigated. The presence of just nitrogen resulted in an increase of the fluorescence quantum yield, without, however, affecting the energy levels. Lateral π-extension of the nanographenes, instead, resulted in a modulation of the excited states energy, which leads to a thermally-activated dual fluorescence with quantum yields as high as 61%. In the corresponding coordination complexes, lateral π-extension resulted in a ping-pong energy transfer cascade, that is, from the nanographene to the metalloporphyrin and back to the nanographene. The results help to directly rationalize properties observed in both graphene quantum dots and nanoribbons. Moreover, they prove that molecular nanographenes are appealing components for solar energy conversion schemes, where the modulation of inter-component energy transfer is of utmost importance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: anti-Kasha emission; coordination complexes; energy transfer; metalloporphyrin; molecular nanographenes

Towards understanding the competition of electron and energy transfer in “molecular” nanographenes on the example of hexa-peri-hexabenzocoronene - Beneventi, Giovanni Mariano; Krug, Marcel; Reger, David; Jux, Norbert; Guldi, Dirk Michael (Journal of Photochemistry and Photobiology C-Photochemistry Reviews, 2023)
Bottom-up strategies have allowed the synthesis of “molecular” nanographenes with full control over size, shape and functionality. In recent years, the progress on wet chemical approaches, oxidative cyclodehydrogenation amongst all, has been the foundation to the synthesis of an impressive number of soluble and well-defined molecular nanographenes. The level of control over nanographene syntheses has allowed a fine-tuning of the photophysical and electrochemical properties and, in turn, has a compelling potential in the field of material science. In this regard, understanding and harnessing the competition between electron transfer and energy transfer in nanographenic systems is of utmost importance. However, a comprehensive structure-property relationship remains still an open aspect. In the present review we describe a large variety of hexa-peri-hexabenzocoronene (HBC)-based nanographenes obtained through wet chemical strategies and linked – either covalently or non-covalently – to porphyrins, rylenes, fullerenes, etc. Particular attention was placed on the optical, electrochemical and excited-state properties.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Electron transfer; Energy transfer; Hexa-peri-hexabenzocoronene; Nanographene; Polycyclic aromatic hydrocarbons